From visual rhetoric to multimodal argumentation: exploring the rhetorical and argumentative relevance of multimodal figures on the covers of The Economist. (August 2021) - Tseronis, Assimakis
Visual rhetoric is more often than not identified with the search for patterns of visual form and content which convey meaning in ways that resemble the meaning construed by known rhetorical figures. Despite the numerous proposals for the classification of figures construed verbally or visually, there has been no systematic attempt to account for the different ways in which these may contribute to the argumentative structure of persuasive messages. In this article, the author studies comparatively the figures of metaphor, antithesis and allusion, cued visually or verbo–visually in the multimodal genre of front covers. He starts from the assumption that the front cover constitutes a multimodal argument in the sense that it invites the reader to buy the specific issue on the grounds of the featured story and the stance that the editors express over it. The goal is to identify the semiotic configurations that distinguish one figure from the other, and to establish conditions under which these figures can be shown to contribute meaning that serves the argument conveyed by the front cover.